Simple multiple reference frame for high-order solution of hovering rotors with and without ground effect - Silva, Paulo A. S. F.; Tsoutsanis, Panagiotis; Antoniadis, Antonis F. (Elsevier, 2021)
In the present work, the aerodynamic performance of the Caradonna and Tung and S-76 in hover were investigated using a simplified concept of multiple reference frame (MRF) technique in the context of high-order Monotone Upstream Centred Scheme for Conservation Laws (MUSCL) cell-centred finite volume method. In the present methodology, the frame of reference is defined at the solver level by a simple user input avoiding the use of mesh interface to handle the intersections between frames of reference. The calculations were made for both out-of-ground-effect (OGE) and in-ground-effect (IGE) cases and compared with experimental data in terms of pressure distribution, tip-vortex trajectory, vorticity contours and integrated thrust and torque. The predictions were obtained for several ground distances and collective pitch angle at tip Mach number of 0.6 and 0.892
Keywords: Ground effect; OGE; IGE; CFD; Rotorcraft; High-order methods